New record of Notocrypta feisthamelii alysos (Moore, 1866) (Lepidoptera: Hesperiidae)- spotted demon from Jammu and Kashmir, India - Kewal Singh; Taslima Sheikh (Journal of Fauna Biodiversity)
This study reports the first record of Notocrypta feisthamelii alysos (Moore, [1866]) Spotted Demon, from the Lohai Malhar Tehsil of District Kathua in Jammu and Kashmir, India. The butterfly and day-flying moth survey, conducted from March to June 2024, revealed the presence of this species, marking a significant addition to the butterflies fauna of Jammu and Kashmir, India. This paper details the observations, habitat, and potential ecological implications of this newly reported butterfly.